Analisis Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Dana Perimbangan Terhadap Belanja Daerah di Kabupaten Kota Provinsi Jawa Timur 2016 – 2022 - Anindya Zahra Meiriana; Sahastian Ayu Kusumaningtyas; Annisa Latifa Pangestuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The challenges faced by Bojonegoro and Tuban counties are high poverty rates and inadequate infrastructure, which continue to occur year after year. The large budgets for Regional Original Income (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK) and Balancing Funds (DP) are some of the reasons why Bojonegoro Regency and Tuban Regency have infrastructure and poverty problems. This research is quantitative using panel data regression and processed using E-Views 12 to examine the relationship between variables. The results of this research are that the levels of Regional Original Income (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK) and Balancing Funds (DP) have a significant positive impact on regional spending.